2019
DOI: 10.1038/s41598-019-44331-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale reorganization of sarcoplasmic reticulum in pressure-overload cardiac hypertrophy visualized by dSTORM

Abstract: Pathological cardiac hypertrophy is a debilitating condition characterized by deleterious thickening of the myocardium, dysregulated Ca 2+ signaling within cardiomyocytes, and contractile dysfunction. Importantly, the nanoscale organization, localization, and patterns of expression of critical Ca 2+ handling regulators including dihydropyridine receptor (DHPR), ryanodine receptor 2 (RyR2), phospholamban (PLN), and sarco/endoplasmic reticulum Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…dSTORM super-resolution imaging. Direct stochastic optical reconstruction microscopy was carried out as described previously 28 . Briefly, stochastic photoswitching of immunostained samples was initiated with a buffer containing 50 mmol L −1 2-mercaptoethylamine (M9768, Sigma-Aldrich), 40 µg mL −1 catalase (C3155, Sigma-Aldrich), 500 µg mL −1 glucose oxidase (G7141, Sigma-Aldrich), 50% (w/v) D-glucose (Sigma-Aldrich), in PBS pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…dSTORM super-resolution imaging. Direct stochastic optical reconstruction microscopy was carried out as described previously 28 . Briefly, stochastic photoswitching of immunostained samples was initiated with a buffer containing 50 mmol L −1 2-mercaptoethylamine (M9768, Sigma-Aldrich), 40 µg mL −1 catalase (C3155, Sigma-Aldrich), 500 µg mL −1 glucose oxidase (G7141, Sigma-Aldrich), 50% (w/v) D-glucose (Sigma-Aldrich), in PBS pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) re-uptakes Ca 2+ from the cytosol into intracellular stores and has been shown to colocalize with RyRs at z-disks (Drago et al, 1998; Eisner et al, 2017; Hadipour-Lakmehsari et al, 2019). SERCA (or effluxing NCX) located near a releasing RyR cluster might alter Ca 2+ diffusion into the imaging plane by reducing signal amplitude or symmetry (depending on the orientation of these channels in relation to the imaging plane).…”
Section: Discussionmentioning
confidence: 99%
“…There is little information on alterations in jSR motility during HF although disrupted SR networks have been observed in HF models ( Pinali et al, 2013 ), and altered distributions of SR proteins are observed in hypertrophic myocytes ( Hadipour-Lakmehsari et al, 2019 ). Microtubule growth and stability is decreased by the oxidative stress of MI, resulting in enhanced rates of microtubule catastrophe and impaired delivery of K V 4.2 and K V 4.3 potassium channels in mouse ventricular myocytes ( Drum et al, 2016 ).…”
Section: Dyadic Calcium Channel Displacement and Mis-regulation During Cardiac Pathologymentioning
confidence: 99%